Interaction among GRIK2 gene on epilepsy susceptibility in Chinese children. (9th April 2019) - Xiong, Shunjun; Wang, Yanjun; Li, Huijuan; Zhang, Xiaofang
Abstract : Aims: The association of single nucleotide polymorphisms (SNPs) of glutamate receptor 2 (GRIK2) gene, as well as gene‐gene interaction with the risk of early‐onset epilepsy susceptibility, was studied in Chinese children. Methods: Generalized multi‐factor dimension reduction (GMDR) is used to identify the optimal linkage between interaction among four SNPs and early‐onset epilepsy susceptibility. Logistic regression was performed to assess association between four SNPs within GRIK2 gene and the risk of epilepsy. Results: The results show that the risk of epilepsy in the rs4840200‐T allele carriers was significantly higher than CC (CT/TT vs CC), adjusted OR (95% CI) = 1.74 (1.31‐2.20), and the carrier of rs3213607‐A allele was also higher than CC (CG/GG vs CC) with adjusted OR (95% CI) = 1.61 (1.23‐2.10). We did not detect significant association between rs9390754 and rs2235076 within GRIK2 gene and epilepsy risk. In the GMDR analysis for the gene/gene interaction (2‐4 locus models), we found a significant two‐locus model ( P = 0.001) involving rs4840200 and rs9390754. The cross‐validation consistency was 10/10, and the prediction error was 0.632. Participants with rs4840200‐CT/TT and rs9390754‐GA/AA genotype within GRIK2 gene have the highest epilepsy risk, compared to participants with rs4840200‐CC and rs9390754‐GG genotype within GRIK2 gene, OR (95% CI) = 2.42 (1.78‐3.11), after covariates adjustment for age and gender. Conclusions: Both rs4840200‐T and rs3213607‐A, and the interactions between rs4840200 and rs9390754 are related to the increased risk of epilepsy risk.